Rancang Bangun Aplikasi Evaluasi Sekolah Dasar Berdasarkan Standar Nasional Pendidikan Pada Dinas Pendidikan Kota Surabaya - Risa Rahmadya Triwendra; Henry Bambang Setyawan; Yoppy Mirza Maulana (Jurnal Sistem Informasi Universitas Dinamika, 2018)
Education Department Surabaya city agencies are responsible for improving the quality of education. To determine the quality of education evaluation in schools using indicators thats contained in the National Education Standards (SNP) include Content Standards, Standard Process, Graduates Competency Standards, Standards Teachers and Education Personnel, Infrastructure Standards, Standards Management, Standard Funding and Assessment Standards.Indicators in the SNP derived from sub-indicators are 80 sub-indicators to each sub indicator recommendations that are needed by elementary school (SD) Interior, SD Private and Government Elementary School (MI).With the number of schools as many as 463 primary schools, 438 private primary schools, and 151 MI resulted in Elementary Education (Pendas) only evaluates several schools Pendas has a limitation of human resources in evaluating schools as well as the time used to evaluate only three weeks.To overcome these obstacles, the solution that is needed is the creation of applications evaluation elementary schools that can speed the evaluation process of the school. Making these applications follow the stages of the SDLC (System Development Life Cycle) waterfall model. Based on trials that have been done, the application can generate proposals on supervision and facilitation for guidance in improving the quality of education.